4-Aminoquinaldine monohydrate polymorphism: prediction and impurity aided discovery of a difficult to access stable form. Issue 22 (29th October 2015) - Braun, Doris E.; Oberacher, Herbert; Arnhard, Kathrin; Orlova, Maria; Griesser, Ulrich J.
Abstract : Crystal structure prediction studies of 4-aminoquinaldine monohydrate led, 80 years after its first synthesis, to the thermodynamically most stable form under conditions relevant for production and storage. Abstract : Crystal structure prediction studies indicated the existence of an unknown high density monohydrate structure (Hy1 B ° ) as the global energy minimum for 4-aminoquinaldine (4-AQ ). We thus performed an interdisciplinary experimental and computational study elucidating the crystal structures, solid form inter-relationships, and kinetic and thermodynamic stabilities of the stable anhydrate (AH I° ), the kinetic monohydrate (Hy1 A ) and this novel monohydrate polymorph (Hy1 B ° ) of4-AQ . The crystal structure ofHy1 B ° was determined by combining laboratory powder X-ray diffraction data and ab initio calculations. Dehydration studies with differential scanning calorimetry and solubility measurements confirmed the result of the lattice energy calculations, which identifiedHy1 B ° as the thermodynamically most stable hydrate form. At 25 °C the equilibrium of the4-AQ hydrate/anhydrate system was observed at an a w (water activity) of 0.14. The finding ofHy1 B ° was complicated by the fact that the metastable but kinetically stableHy1 A shows a higher nucleation and growth rate. The presence of an impurity in an available4-AQ sample facilitated the nucleation ofHy1 B °, whose crystallisation is favored under hydrothermal conditions. The value of combining experimental with theoretical studies in hydrate screening and characterisation, as well as the reasons for hydrate formation in4-AQ, are discussed.